2020
DOI: 10.1126/sciadv.abb6376
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear landscape and cultural response to sea-level rise

Abstract: Rising sea levels have been associated with human migration and behavioral shifts throughout prehistory, often with an emphasis on landscape submergence and consequent societal collapse. However, the assumption that future sea-level rise will drive similar adaptive responses is overly simplistic. While the change from land to sea represents a dramatic and permanent shift for preexisting human populations, the process of change is driven by a complex set of physical and cultural processes with long transitional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 45 publications
(72 reference statements)
0
20
0
Order By: Relevance
“…A more rigorous assessment of Holocene sea level changes in eastern Saudi Arabia by Parker et al (2020) showed that the transgression rose above mean sea level at about 7000 year BP and the mean highest high tide water level was recorded as up to 3.75 m above present sea level at 5400 year BP. The Late Holocene sea level fall in the Red Sea follows the global sea level pattern (Ramsay and Cooper, 2002;Siddall et al, 2003;Sloss et al, 2018) but differs from that in the Mediteranean Sea where sea level is continuing to rise (Barnett et al, 2020).…”
Section: Sea Level Implicationsmentioning
confidence: 92%
“…A more rigorous assessment of Holocene sea level changes in eastern Saudi Arabia by Parker et al (2020) showed that the transgression rose above mean sea level at about 7000 year BP and the mean highest high tide water level was recorded as up to 3.75 m above present sea level at 5400 year BP. The Late Holocene sea level fall in the Red Sea follows the global sea level pattern (Ramsay and Cooper, 2002;Siddall et al, 2003;Sloss et al, 2018) but differs from that in the Mediteranean Sea where sea level is continuing to rise (Barnett et al, 2020).…”
Section: Sea Level Implicationsmentioning
confidence: 92%
“…They must balance the usual considerations of cost, engineering and social and environmental impact assessment, while also building-in space in their design envelope for habitat provision [ 71 ]. With this balancing act becoming increasingly complex, incorporation of multiscale structural complexity and environmentally sensitive design may be vital for meeting biodiversity targets in the coastal environment [ 37 , 72 ]. Our results highlight the specific scales at which artificial structures are particularly deficient in structural complexity compared to natural shores, and which could be the focus of future targeted interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Although the extent of postglacial sea level change has long been recognised, its impact on Mesolithic communities has received surprisingly limited study and is also a subject of contrasting views. Sea level rise can have positive impacts on hunter-gatherers by increasing the extent of resource-rich inter-tidal areas and providing new routes of travel by expanding sea ways (Barnett et al, 2020). Lewis et al (2020) attributed population growth in Scandinavia to the high levels of marine productivity that arose from a combination of sea level rise and increasing temperature.…”
Section: Resilience To Sea Level Changementioning
confidence: 99%
“…For both past and future sea level rise these impacts disturb invertebrate, fish, bird, and sea mammal communities; they destabilise food-webs with consequences for hunter-gatherer resource availability. Benjamin et al (2017) noted that sea level rise in the Mediterranean Basin flooded coastal sites, displaced fishing and shell fishing grounds, creating isolated environments in the form of new islands, bays, and straits, while Barnett et al (2020) described the increased vulnerability of insular and island communities arising from sea level rise. In northern regions, where isostatic rebound was significant, the fall in relative sea level may have had equivalent environmental and economic impacts.…”
Section: Resilience To Sea Level Changementioning
confidence: 99%